KONSEP PENDIDIKAN KH. NOER ISKANDAR SQ DALAM MENGEMBANGKAN PONDOK PESANTREN - Siti Munawati; Muhamad Mas'ud; Faiz Fikri Al Fahmi (ISLAMIKA, 2023)
Islamic boarding schools as one of the faith-based education, also function as Islamic religious broadcasters. Islamic boarding schools have a high level of integrity with sekitamya and become a moral show for the general public. The science studied is inseparable from religious teachings, meaning that all events that occur are considered to have a relationship with religious teachings. The educational institution built by kiayai Noer Iskandar SQ is the Asshiddiqiyah Islamic Boarding School which is an Islamic educational institution and a religious social institution. In its capacity as an Educational, Religious, and Community institution, Asshiddiqiyah Islamic Boarding School always exists in developing its educational concept and remains committed as a stronghold of the Islamic shiar struggle. The method that the author used in this study is the qualitative method. The reason researchers use this is because in this paper, the author wants to provide, explain, describe the concept of pesantren education thought developed by KH. Noer Iskandar SQ who critically, or describes a phenomenon, an event, or an event of social interaction in pesantren. Therefore, this type of qualitative research is descriptive, by collecting field data and existing literature. The difference between one type and another lies in the purpose and strategy of discovery.